1997
DOI: 10.1159/000246050
|View full text |Cite
|
Sign up to set email alerts
|

Excess Benign Melanocytic Naevi in Renal Transplant Recipients

Abstract: Background: Some studies indicate that malignant melanoma occurs more frequently in renal transplant recipients than in the normal population. The development of excess benign melanocytic naevi is regarded as an indicator of the risk for malignant melanoma. Objective: This study was undertaken to evaluate the prevalence of benign melanocytic naevi in adult renal transplant patients. Method: All benign melanocytic naevi irrespective of size were counted in 76 patients with renal transplants and were compared to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Transplant recipients are particularly predisposed to the development of skin cancer [1,2,3, 11]. Although the UV radiation is the only trigger factor of skin neoplasia which could be effectively avoided, the knowledge about the harmfulness of sunlight exposure and about the need of sun protection among the studied RTR appeared to be scanty.…”
Section: Discussionmentioning
confidence: 99%
“…Transplant recipients are particularly predisposed to the development of skin cancer [1,2,3, 11]. Although the UV radiation is the only trigger factor of skin neoplasia which could be effectively avoided, the knowledge about the harmfulness of sunlight exposure and about the need of sun protection among the studied RTR appeared to be scanty.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in a case-control study conducted within an adult RTR population, where the authors found an increase in the average number of melanocytic naevi in the RTR population compared with controls (93.6 Ϯ 52.2 vs 36.1 Ϯ 29.9). 19 This difference was again most pronounced on the palms and soles (with a ratio of absolute numbers of naevi between the RTR population and controls of 4.0) as well as the back/ buttocks (ratio of 3.3).…”
Section: Risk Factorsmentioning
confidence: 95%
“…In a single western study involving 76 RTRs, the mean total number of benign melanocytic nevi was significantly higher in RTR compared to the normal population. [19] In Western studies, the incidence of cutaneous malignancies among RTR varied from 8% at 1 year to 44% at 15 years. [20][21][22] The cumulative effect of viral infections, prolonged immunosuppression and sunlight has been thought to predispose to the development of skin cancer in the transplant population.…”
Section: Skin Lesions In Rtrmentioning
confidence: 99%